Sosiodrama untuk meningkatkan kecerdasan moral pada siswa sekolah menengah pertama - Ana Mutiya; Zainul Anwar; Ni’matuzahroh Ni’matuzahroh (Cognicia, 2019)
Moral intelligence is a person's ability to determine right behavior and wrong behavior. High moral quality is needed as a benchmark for successful children in their social life. Students who have moral intelligence that is low in integrity in students are not formed, lack responsibility, do not think about other people's feelings when they hurt or behave, and easily act as desired. Lennick and Kiel formulated moral intelligence in four aspects, namely: integrity, responsibility, compassion, and forgiveness. The increase of a behavioral determination is not limited to instinct or children learning independently but from a character education. Sociodrama can be one method of increasing moral intelligence, because there are supporting indicators in sociodrama. This study aims to determine the effect of sociodrama methods on increasing moral intelligence in junior high school students. The research subjects were 26 who were divided into two control groups and the experimental group who had moderate and low scores on moral intelligence. This study used a quasi experiment with a control group design pre-test and post-test. Data analysis used paired sample t test, the results showed a difference between the pre-test and post-test score (r = 21,923 and p = 0,000 (p <0,05), so it can be concluded that the results of the study indicate a significant change from sociodrama intervention in improving moral intelligence in junior high school students.